2x - 4 = -10 2x = -10 +4 2x = -6 x = -3
-1-2x-4x=19-6x-1 = -19x = 3
3x-2 = 2x+3 3x-2x = 3+2 x = 5
-2y square exp power -2x-1
13
If you solve such an equation for "y", you get an equation in the slope-intercept form.
You cant solve it unless it is an equation. To be an equation it must have an equals sign.
(2x)ysquared
2x - 4 = -10 2x = -10 +4 2x = -6 x = -3
You cannot solve one equation in two unknowns.
This is already the equation. Now you just have to solve it. x=5.
I would use substitution. Turn the second equation into y=8-2x, put it into the first and solve for x. Then put x into one of the equations and solve for y.So...2x-3(8-2x)=24 --> 2x-24+6x=24 --> 8x=48 --> x=6y=8-(2x6) --> y=8-12 --> y=-4
Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4
2x-3=9 so 2x=12 and x=6
Where is y in this equation? 2x-3=9. First, you add 2 to both sides, and you get 2x=12. Divide both sides by 2; so, x=6.
x=12
-1-2x-4x=19-6x-1 = -19x = 3